(untitled) (Global Journal of Science Frontier Research, 2020)
The paper considers a mechanism of the elimination of the film boiling process during intensive quenching (IQ) of steel parts in water polymer solutions of low concentration. The use of the IQ process results in improvement of material mechanical properties and steel part performance characteristics. Evaluation of ways of eliminating of the film boiling process using a modern physics point of view allows significant improvement of the IQ equipment making it less costly and more efficient. All of this cardinally simplifies the implementation of the IQ technology in heat treat practice. The paper shows how creation of a thin insulating surface layer during quenching of steel parts in low concentration of inverse solubility polymers results in eliminating of film boiling processes that makes the quench process intensive. Historically in heat treating industry, an effective heat transfer coefficient was widely used for evaluating of the nucleate boiling process. And quenching during the nucleate boiling mode of heat transfer was considered as slow cooling.